“Liberty for Androids!”: Player Choice, Politics, and Populism in Detroit: Become Human - Stefan Schubert (European Journal of American Studies)
In this article, I analyze the 2018 video game Detroit: Become Human as a potentially political text from the perspective of literary and cultural studies. I argue that it features and presents narrative choices in a way that encourages players to make decisions not solely for personal or empathetic reasons but also through a political contemplation, and I contend that the manner in which the game narratively presents individual agency and populist imaginations of “the people” complicates this political project. To do so, I first present an approach to narrative, agency, and politics in video games more generally, before then discussing questions of agency and politics in Detroit: Become Human on three levels: in its narrative presentation, in how the gameplay politicizes player choice, and in how both the narrative and the ludic elements in the game complicate its interest in politics. This contribution thus suggests ways of both studying the connections of agency and politics in video games and culturally contextualizing this particular way of representing (a)political choices.